An Analysis of Problem Solving Ability in Social Studies Subject Using Problem Based Learning Model - Dian Ayu Larasati; Agung Dwi Bahtiar El Rizaq; Sujatno; Sea Thearith (Universitas Negeri Surabaya, 2025)
This research aims to compare problem solving skills taught through Problem Based Learning with direct learning using Geogebra software. This research is a type of quasi-experimental research. All participants in this research were class VIII students at SMP Negeri 11 Surabaya. The description test with ten questions is a research tool used to assess problem solving skills. The research used Covariance Analysis (Anacova), inferential analysis of the data was carried out. The research results show that students who use the problem-based learning model with GeoGebra software have better problem solving abilities compared to students who use the direct learning model with GeoGebra software